2017
DOI: 10.3310/hsdr05250
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effectiveness of annual health checks and quality of health care for adults with intellectual disability: an observational study using a primary care database

Abstract: Background People with intellectual disability (ID) have poorer health than the general population; however, there is a lack of comprehensive national data describing their health-care needs and utilisation. Annual health checks for adults with ID have been incentivised through primary care since 2009, but only half of those eligible for such a health check receive one. It is unclear what impact health checks have had on important health outcomes, such as emergency hospitalisation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 119 publications
1
35
0
Order By: Relevance
“…b Start date is the latest of either the date of the patient's registration at the general practice or the date that the general practice began using vision software. R Date date of patient's registration in the GP, ASD Dx autism spectrum disorder diagnosis, Psych Rx psychotropic drug prescription, NC Dx neuropsychiatric comorbidity diagnosis (University of Cambridge) and published studies (Barnett et al 2012;Murray et al 2014;Hire 2016;Carey et al 2017), and the descriptions of the codes have been reviewed by a psychiatrist in our research team.…”
Section: Neuropsychiatric Comorbiditiesmentioning
confidence: 99%
“…b Start date is the latest of either the date of the patient's registration at the general practice or the date that the general practice began using vision software. R Date date of patient's registration in the GP, ASD Dx autism spectrum disorder diagnosis, Psych Rx psychotropic drug prescription, NC Dx neuropsychiatric comorbidity diagnosis (University of Cambridge) and published studies (Barnett et al 2012;Murray et al 2014;Hire 2016;Carey et al 2017), and the descriptions of the codes have been reviewed by a psychiatrist in our research team.…”
Section: Neuropsychiatric Comorbiditiesmentioning
confidence: 99%
“…Olsen et al (1976) found a significant difference between the treatment group (health check recipients) and the control group (non-recipients) in terms of an increase in the number of night hospitalizations for the treatment group. In a study of adults with intellectual disabilities, health check-ups reduced preventable emergency admissions (Carey et al, 2016(Carey et al, , 2017. Our empirical analyses make use of a data set that was provided by the KNHIS.…”
Section: Effects Of General Health Checks On Healthcare Utilizationmentioning
confidence: 99%
“…Health checks in persons with learning disability were associated with lower hospital admissions for ambulatory care sensitive conditions (IRR 0.82, 95% CI 0.69 to 0.99), the conditions for which hospital admission could be prevented by effective healthcare intervention. They found no significant difference in overall emergency hospital admissions, but there was evidence for greater impact in those with severe health needs (IRR 0.80, 95% CI 0.67 to 0.95) (Carey et al., 2017a). Their analysis matched on age, sex and practice, and their results were stratified by individual characteristics, including sex, age band, down syndrome, communal accommodation, autism, epilepsy and severe health needs (Carey et al., 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…They found no significant difference in overall emergency hospital admissions, but there was evidence for greater impact in those with severe health needs (IRR 0.80, 95% CI 0.67 to 0.95) (Carey et al., 2017a). Their analysis matched on age, sex and practice, and their results were stratified by individual characteristics, including sex, age band, down syndrome, communal accommodation, autism, epilepsy and severe health needs (Carey et al., 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation